ISOLASI DAN KARAKTERISASI MIKROBA PENGHASIL ANTIBIOTIK DARI RIZOSFER TANAMAN KECIPIR (PSOPHOCARPUS TETRAGONOLOBUS) DAN PISANG (MUSA PARADISIACA) - Hasibuan, Sari Yulia Kartika; Jaya, Dori Kusuma; Ansiska, Paisal; Bria, Deseriana; Aprianto, Dodi (Jurnal Agroteknologi dan Pertanian (JURAGAN), 2021)
Many microbial populations are found in the rhizosphere, including in the soil layer that follows the plant root system. Rhizosphere soils contain more bacteria, fungi and actinomycetes than non-rhizosphere soils. One of the antibiotic producing bacteria has been isolated from the rhizosphere. The purpose of this study was to isolate and characterize the biochemistry of antibiotic producing bacteria and to evaluate their superiority in inhibiting other types of bacteria. Three microbial isolates were isolated from the rhizosphere of winged bean (K) and banana (P1 and P2) plants. All isolated isolates were tested for antagonism with E. coli, Bacillus, and Pseudomonas bacteria on Nutrient Agar (NA) media to determine antibiotic-producing bacteria. Furthermore, identification and characterization of colony morphology and a series of antagonism and pathogenicity tests were carried out. The three isolates had irregular colony forms (isolates K and P1) as well as oval shapes (isolate P2), flat surface, glossy texture, milky white or cream color, and irregular edges. The antagonism test showed that isolates P1, P2, and K could inhibit the growth of bacterial colonies E. coli, Bacillus, and Pseudomonas, respectively. In the pathogenicity test, the three microbial isolates did not show symptoms of necrosis in tobacco leaves after 2 days of observation.